E-comic as a media to build an understanding of newtons concepts - Khoiri, Nur; Lilyani, Feby Sella Tutut; Wijayanto, Wijayanto (Universitas PGRI Kanjuruhan Malang, 2024)
This research aims to create effective physics e-comic learning media to help students understand Newtonâ€™s concepts. The Research and Development methodÂ was used in conjunction with a 4-DÂ development model that consists of four stages: definition, design, development, and dissemination. At the definition stage, a series of needs analysis was carried out, collecting and analyzing information. After a series of definitions had been formulated, the next step was to design. This stage involved designing the product that would be created in accordance with the previously completed definition formula. After the design stage was completed, the designing stage consisted of two steps, namely expert appraisal (expert assessment), accompanied by revisions and developmental testing (development trials) up to the deployment stage. A limited trial on 27 students of class VIII from SMP Negeri 15 Semarang resulted in an increase of 80% in student learning outcomes in final physics learning with the criteria â€œvery feasible.â€ Based on limited trials, the e-comic media developed was effective and could be used as a physics learning medium to build understanding of Newtonian material physics concepts. This research couldÂ serve as a foundation for several other studies that employed diverse and innovative learning media, such as e-comics, which couldÂ have ramifications for readersâ€™ understanding of several concepts related to their cognitive abilities.